The Feasibility and Method of Providing Financial education in Higher Vocational Colleges - Xie, Ximei (Journal of Theory and Practice of Management Science, 2023)
The concept of inclusive finance is the core content of deepening the reform of the financial supply side under the background of the new era. The first prerequisite for comprehensively implementing inclusive finance is to strengthen individual financial literacy through the innovation of financial theory publicity mode. In this process, higher vocational colleges play an irreplaceable role, which can not only meet the basic requirements of financial literacy of target groups, but also guarantee the comprehensive development of higher vocational colleges and form a good situation of mutual benefit and symbiosis.